How Temperature Shapes Diode Performance: An Experimental Study on Rectifier, Avalanche, and Zener Diodes - Lee, Mei Chi; Purnamasari, Indah; Kovalenko, Kirill (Schrödinger: Journal of Physics Education, 2026)
Purpose of the study: The purpose of this study is to experimentally analyze the effect of temperature on the internal resistance of rectifier, avalanche, and Zener diodes by measuring their current–voltage characteristics across different operating temperatures. Methodology: This study employed an experimental method using two digital multimeters (Sanwa CD800a), a K-type thermocouple (Omega), a DC power supply (GW Instek GPS-3030), an aluminum container, and an electric heater. Data were recorded manually and analyzed using Microsoft Excel for I–V plotting and temperature coefficient calculations. Main Findings: The rectifier, avalanche, and Zener diodes exhibited distinct I–V characteristics and temperature-dependent behavior. Maximum forward currents were 264.8 mA (rectifier), 299.4 mA (avalanche), and 37.25 mA (Zener). Temperature coefficients showed negative values for avalanche diodes and positive values for Zener diodes. Internal resistance increased with temperature for all diodes, with rectifier Rd ranging from 0.185 Ω to 0.2 Ω, avalanche Rd from 0.233 Ω to 0.25 Ω, and Zener Rd from 0.1 Ω to 0.125 Ω. Novelty/Originality of this study: This study presents a novel experimental comparison of rectifier, avalanche, and Zener diodes by simultaneously evaluating internal resistance and temperature resistivity coefficients under identical thermal conditions. The results provide new empirical insights into diode-specific thermal behavior, advancing current knowledge on temperature-sensitive performance in practical electronic applications.